Energy auditing in Kolej Mawar Universiti Teknologi MARA Shah Alam / Mohamad Suid Ismail - Ismail, Mohamad Suid (2009)
The global warming arouse the awareness of the public in the energy saving. New energy saving technology is appearing and developing rapidly, at the same time energy regeneration or alternative technology is developing in large scale. Basically energy problem can be classified into the following solution in general: energy saving, energy searching and energy recycling. Electricity consumption in Univeristi Teknologi Mara Shah Alam is very high indeed. Bill has reached as high as RM 1.8 million per month. The consumption of electricity came from PTAR, Bangunan Canseleri, hostels, Pusat Islam, Bangunan Sains & Teknologi, Bangunan Pendaftaran and street lighting. Here the application of energy efficiency is very important and this is in line with the government's campaign to encourage people to save the electricity usage.